2018
DOI: 10.1080/13621718.2018.1452875
|View full text |Cite
|
Sign up to set email alerts
|

Effect of pulse scheme on the microstructural evolution, residual stress state and mechanical performance of resistance spot welded DP1000-GI steel

Abstract: In the present study, the effect of resistance spot welding scheme (i.e. single and double pulse welding) on the mechanical behaviour of resistance spot-welded DP1000-GI steel is investigated. It is shown that double pulse welding at low welding current decreases the maximum crosstension strength and mechanical energy absorption capability of the welds. The factors that lead to the lower mechanical performance of double pulse welds are scrutinised. Local residual stress mapping reveals that the compressive res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 35 publications
(13 citation statements)
references
References 17 publications
0
10
0
1
Order By: Relevance
“…Conversely, the one-step RSW has a narrower PMZ. Chabok et al [20] reported that the two-step RSW has two effects on the property of the PMZ. First, the higher heat input would reduce the residual stress of the PMZ and eliminates the compressive stress perpendicular to the plane of the crack.…”
Section: Nugget Diametermentioning
confidence: 99%
“…Conversely, the one-step RSW has a narrower PMZ. Chabok et al [20] reported that the two-step RSW has two effects on the property of the PMZ. First, the higher heat input would reduce the residual stress of the PMZ and eliminates the compressive stress perpendicular to the plane of the crack.…”
Section: Nugget Diametermentioning
confidence: 99%
“…Контролировать термические циклы нагрева и охлаждения объема металла литого ядра Уменьшение скорости охлаждения при формировании сплава должно существенно увеличить время пребывания металла в жидком состоянии и обеспечить равномерное распределение золота по всему объему литого ядра, а также привести к снижению остаточных напряжений [11] и уменьшить вероятность образования внутренних дефектов [7]. Управлять скоростью охлаждения в процессе КТС стало возможно с помощью современных источников питания, позволяющих задавать любую форму импульса тока [12,13].…”
Section: Introductionunclassified
“…Literature demonstrates that mechanical behaviour of spot welded joint is mostly affected by welding current, followed by welding time and electrode force [23]. Furthermore, some process parameters and material conditions such as holding time [24], surface characteristics [25], preheating [26], post heating [27], alloy content [28] and multi pulse [29] are also investigated. However, there is further scope to improve the mechanical performance of spot welded joint by electrode tip diameter.…”
Section: Introductionmentioning
confidence: 99%